Anti-Biofilm and Antimicrobial Activities of Five Edible and Medicinal Macrofungi Samples on Some Biofilm Producing Multi Drug Resistant Enterococcus Strains - Başar Karaca; Arzu Çöleri Cihan; Ilgaz Akata; Ergin Murat Altuner (Turkish Journal of Agriculture: Food Science and Technology)
It is commonly well-known that biofilms are the predominant mode of bacterial growth, reflected in the clinic observations, where approximately 80% of all bacterial infections are related to biofilms. Bacteria in biofilms are well protected against environmental stresses, antibiotics, disinfectants and the host’s immune system and are usually extremely difficult to eradicate. Due to common problems caused by biofilms, alternative anti-biofilm strategies must be developed. Enterococcus strains are able to form complex surface-associated communities (biofilms), which contribute to its resistance and persistence in both host and non-host environments, and are especially important in food processing and clinical environments. Enterococcus biofilms showed increased antimicrobial resistance to the most of antibiotics as compared to the planktonic bacteria, which make them difficult to combat. There is an increasing evidence that biofilms are often associated with infectious diseases. Novel anti-biofilm strategies must be designed to include natural bio products instead of common antibiotics. Mushrooms are a nutritionally functional foods and a source of pharmaceuticals having functions such as antitumor, immunomodulating, antioxidant, cardiovascular, anti-hypercholesterolemia, antiviral, antibacterial, anti-parasitic, antifungal, detoxification, hepatoprotective, and antidiabetic. In addition, they have a notable activity against biofilms. In this study, the antimicrobial and anti-biofilm activities of some medicinal and edible mushrooms, namely Morchella angusticeps Peck, Ganoderma lucidum (Curtis) P. Karst., Cerioporus squamosus (Huds.) Quél., Trametes versicolor (L.) Lloyd and Lentinula edodes (Berk.) Singer were screened against multi drug resistant Enterococcus strains. As a result, it was observed that these mushrooms have notable potency to develop alternative medicines to struggle infectious diseases and biofilms.